Piezoelectric properties of Mn-doped 0.75BiFeO3–0.25BaTiO3 ceramics. Issue 8 (June 2016) - Joo, H.W.; Kim, D.S.; Kim, J.S.; Cheon, C.I.
Abstract: The effects of Mn doping were investigated in 0.75BiFeO3 –0.25BaTiO3 ceramics sintered at 940–1020 °C in air. 0.75BF–0.25BT ceramics doped with 0–0.7 wt% MnO2 were prepared by a conventional ceramic process. The effects of the doping are strongly dependent on the sintering temperature and doping concentration. MnO2 doping at less than the solubility limit of 0.5 wt% suppressed the formation of large pores during the sintering, and kept the sample dense at high sintering temperatures. The onset temperature of abrupt grain growth also increased. The piezoelectric properties were poor when the grain size was about 1 µm or less, but showed a significant increase in samples with grain size greater than a few micrometers, independent of the Mn doping concentration. The piezoelectric properties are more strongly influenced by the grain size than the Mn doping.